Is the Special Judo Fitness Test (SJFT) Index discriminative for children? - Courel-Ibanez, J.; Escobar-Molina, R.; Ibanez, D.; Franchini, E. (Revista de Artes Marciales Asiaticas, 2016)
In the last 20 years, judo coaches and researches have widely used the SJFT (Sterkowicz, 1995), considered one of the basic instruments in monitoring the training progress of highly qualified competitors. The test is performed on the tatami with three judo practitioners from approximately the same weight categories. The athlete who is being tested stands in between the other two athletes, who are positioned 3 m apart from the tested subject on opposite ends. At the Hajime command, the subject attempts at throwing the two assistants by Ipon-seo-nageh in three separate series: 15 seconds the first, while Series 2 and 3 last 30 seconds each. There are two 10 second breaks between the series. Its resulting index . formula based on total of throws (TT) and heart rate (HR) . seems to be reliable and consistent tool for physical condition assessment in junior and senior athletes. Nevertheless, there is a lack of reports about the use and efficiency of this test in children (Drid, Trivi., & Tabakov, 2012). Thus, the aim of the present study was to perform SJFT in children to analyse differences between groups of age and competition level.